Risk and severity of psoriasis vulgaris in relation to angiotensin II type 1 receptor gene polymorphism and metabolic syndrome - ElGhareeb MI; Khater MH; Fakhr A; Khedr HAE (Dove Medical Press, 2019)
Mohamed Ibrahim ElGhareeb,1 Mohamed Hamed Khater,1 Ahmed Fakhr,2 Hanaa Abd-Elftah Khedr3 1Dermatology and Venereology Department, Faculty of Medicine, Zagazig University, Zagazig, Egypt; 2Microbiology, Molecular Biology and Immunology Department, Faculty of Medicine, Zagazig University, Zagazig, Egypt; 3Dermatology Department, Al Ahrar Hospital, Zagazig, EgyptCorrespondence: Mohamed Ibrahim ElGhareebDermatology and Venereology Department, Faculty of Medicine, Zagazig University, Zagazig, EgyptTel +20 109 290 7455Email moh_elghareeb@yahoo.comBackground: Psoriasis vulgaris is a chronic inflammatory and proliferative skin disease, characterized by the formation of itchy, erythematous skin patches or plaques. Patients with psoriasis are at an increased risk of developing metabolic syndrome, including obesity, hypertension, diabetes, and atherosclerosis. Recently, angiotensin II (Ang II) has been reported to be associated with the development of psoriasis. Ang II not only increases the blood pressure but is also a potent proinflammatory modulator and functions through interaction with angiotensin II type 1 receptor (AT1R). Moreover, it is hypothesized that the AT1R gene expression could be correlated with the severity of psoriasis and/or metabolic syndrome.Aim: We examined the association of Ang II type 1 receptor (AT1R) A1166C gene polymorphisms and metabolic syndrome with the severity of psoriasis.Patients and methods: The present case-control study included 25 patients with psoriasis vulgaris and 25 healthy subjects in Egypt. The psoriasis lesions in the patient group were assessed using the psoriasis area and severity index (PASI) score. The AT1R polymorphism A1166C (rs5186) was studied using restriction fragment length polymorphism (RFLP) and polymerase chain reaction (PCR) amplification of the gene from the whole blood sample in both groups. Serum lipid profile and blood sugar levels were assessed post 12 h and 8 h fasting, respectively, in both groups. The severity of metabolic syndrome was evaluated using the severity score.Results: The results of the present study demonstrated that the AT1R A1166C gene polymorphisms increased the risk of developing psoriasis in the Egyptian population. We found that 70% of patients with AC genotype and 100% of patients CC genotype reported a PASI score >20 and were considered to be severe cases with a statistically significant difference as compared with patients with AA genotype (p=0.003). In addition, a high statistically significant difference (p=0.001) existed among AT1R genotypes with respect to the percentage of metabolic syndrome in psoriasis patients. Similarly, a statistically significant difference (p=0.004) among AT1R genotypes with respect to metabolic score was found, with the highest level of score and percentage observed in patients with CC genotype than in patients with AC genotype. The lowest level was present among those with AA genotype.Conclusion: Patients with psoriasis expressing the C allele of AT1R1166 are susceptible to developing metabolic syndrome and have higher PASI scores as compared with patients carrying the A allele.Keywords: psoriasis, metabolic syndrome, angiotensin receptor, gene polymorphism